The Use of Local Landscape as a Field Laboratory for Geography of Education - Ruli As'ari; Erni Mulyanie (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2019)
Geographical skills that need to be shared by each geographer in general are map skills, field skills, and satellite image interpretation skills. To achieve field skills competency, a location is needed to be used as material for practicum studies for each subject. The Geography Education Field Laboratory can be studied in depth based on an analysis of the level of learning needs. The basis of the lab location requirements as a laboratory is seen from the laboratory function as an area to carry out careful and accurate testing and measurement of the phenomenon under study. The study was carried out through the identification of local landscapes by delineating the area through the utilization of satellite citera, and identifying potential from each area that was chosen descriptively. In this study, the Gunung Galunggung area can be used as a Physical Field Laboratory for Geography and Kampung Naga Education can be used as a Field Laboratory for Social and Cultural Geography.